A Future History of Water - Ballestero, Andrea (Duke University Press, 2019)
Based on fieldwork among state officials, NGOs, politicians, and activists in Costa Rica and Brazil, A Future History of Water traces the unspectacular work necessary to make water access a human right and a human right something different from a commodity. Andrea Ballestero shows how these ephemeral distinctions are made through four technolegal devices-formula, index, list and pact. She argues that what is at stake in these devices is not the making of a distinct future but what counts as the future in the first place. A Future History of Water is an ethnographically rich and conceptually charged journey into ant-filled water meters, fantastical water taxonomies, promises captured on slips of paper, and statistical maneuvers that dissolve the human of human rights. Ultimately, Ballestero demonstrates what happens when instead of trying to fix its meaning, we make water's changing form the precondition of our analyses.